Rättvisemärkning av snittblommor på den svenska marknaden - Ahlberg, Stina (2007)
Trade is the driving force for economic development. A greater equity in international trade can improve the livelihoods and the well being of producers in developing countries. The small-scale farmers have limited resources and have difficulties to get access to the international market. As a result of this, the Fair Trade movement has been developed and has now formed a trading partnership between the producer and the consumer.